The effect of anti-neutrophil cytoplasm autoantibodies on the signal transduction in human neutrophils. - Lai, K N (1991)
The effect of anti-neutrophil cytoplasm autoantibodies (ANCA) on neutrophil activation was studied by pre-incubating neutrophils with IgG and F(ab')2 prepared from ANCA patients with Wegener's granulomatosis or microscopic polyarteritis. We measured the generation of inositol triphosphate (IP3) (a product of hydrolysis of membrane phospholipid which acts as a second intracellular messenger), and the translocation of protein kinase C (PKC) upon stimulation by a chemotactic peptide, fMet-Leu-Phe (fMLP). ANCA+ F(ab')2 did not induce a significant increase in IP3 generation. Nonetheless, ANCA+ F(ab')2 and ANCA+ IgG pretreatment of human neutrophils reduced the production of inositol phosphates upon subsequent fMLP stimulation compared with experiments performed when cells were pretreated with F(ab')2 and IgG prepared from ANCA- healthy subjects. A significantly reduced generation of IP3 and inositol biphosphate (IP2) was observed. ANCA+ F(ab')2 pretreatment of neutrophils inhibited fMLP-stimulated IP3 generation in a dose-dependent manner. The membrane-bound PKC activity upon stimulation by FMLP and PMA was reduced in neutrophils pretreated with ANCA+ F(ab')2 and IgG. These results indicate that ANCA affect in vitro signal transduction (IP3 generation, and translocation of PKC) in human neutrophils. Apparently, further activation of signal transduction by chemotactic peptide is significantly blunted in cells pre-incubated with ANCA+ F(ab')2 but not with F(ab')2 from healthy controls.